A Domino Ring-Closure Followed by Retro-Diels-Alder Reaction for the Preparation of Pyrimido[2,1-a]isoindole Enantiomers - Fekete Beáta (EUROPEAN JOURNAL OF ORGANIC CHEMISTRY, 2016)
A simple method was developed to prepare pyrimido[2,1-a]isoindole derivatives by using di-endo- and di-exo-ethyl 3-aminobicyclo[2.2.1]hept-5-ene-2-carboxylate enantiomers as chiral sources. The method is based on a domino ring-closure reaction of norbornene 2-aminohydroxamic acid followed by microwave-induced retro-Diels-Alder reaction. In the case of enantiomeric starting substances, the chirality is transferred from norbornene derivatives to pyrimido[2,1-a]isoindoles. The configurations of the synthesized compounds were determined by 1D and 2D NMR spectroscopy [based on 2D NOE cross-peaks and (3)J(H,H) coupling constants] and X-ray crystallography.